Serum Copper And Hepatic Copper In Chronic Liver Diseases With Particular Reference To Indian Childhood Cirrhosis - NISHA P. MALIK; V.K. SHARMA; MEDHA JAIN; V.K. SHARMA; SHWETA GARG; ASHUTOSH SINGH (International Journal of Pharma and Bio Sciences, 2012)
Sixty five patients (20 children and 45 adults of both sexes) having hepatomegaly were subjected to serum copper, hepatic copper and hepatic cuproprotein analysis from October 1982 through September 1983. Higher levels of serum copper were encountered in 17/20 children suffering from Indian Childhood Cirrhosis (ICC), values ranging from 151 ug/dl to 350 ug/dl. Hypercupremia was also detected in reactive hepatitis 5/17, portal cirrhosis 2/9, chronic active liver disease (CALD) ¾, malignancies in liver 3/5 and in the single case of secondary biliary cirrhosis, serum copper was normal in cases of steatosis of liver, Dubin-Johnson Syndrome and congenital hepatic fibrosis.Hepatic copper was detected only in cases of ICC (17/20). Hepatic cuproproteins were also detected in all these cases as intracytoplasmic dark drown granules. In other chronic liver diseases studied, both hepatic copper and cuproproteins were negative. It is proposed that deranged copper metabolism could have a role in the pathogenesis of ICC.